PEMBATALAN PUTUSAN ARBITRASE AKIBAT DITEMUKANNYA DOKUMEN MENENTUKAN YANG DISEMBUNYIKAN: STUDI PUTUSAN MA NO. 470B/PDT.SUS-ARBT/2022 - Taufik, Harven Filippo (Masalah-Masalah Hukum, 2024)
Arbitral awards may be annulled if a decisive document, hidden by the opposing party, is later discovered. In PT. PLN (Persero) vs. PT. Sumsel Energi Gemilang, the Supreme Court rejected this argument, stating the document did not meet the criteria. This paper examines the requirements for such documents to justify annulment. Using doctrinal legal research with statutory, conceptual, and case-based approaches, it was found that arbitration awards, though final and binding, can be annulled if hidden documents present new information not revealed during arbitration. However, documents whose substance was implied or included in other records cannot be used as grounds. As the Supreme Court's interpretation is not explicitly regulated by law, legal reform is necessary to clarify the definition of “hidden decisive documents”.